Choice reviews - Association of College and Research Libraries ([Middletown, Conn.] : Association of College and Research Libraries)
Consisted of a searchable database of reviews issued in the print magazine Choice (Chicago, Ill.) since Sept. 1988. Beginning with vol. 44, no. 1 (Sept. 2006), resource also includes editorial content from print version.
Title from main menu (choicereviews.org, viewed February 20, 2018).
Annual cumulated index included in the last issue of each volume.
Selected reviews listed annually in: Outstanding academic books and nonprint materials.
Keywords: Best books -- Periodicals; Best books -- Databases; Academic libraries -- Periodicals; Academic libraries; Best books; Electronic journals